Lambrinos, Lambros - (:unkn) unknown (My University, 2026)
Lampros Lamprinos is a Αssistant Professor in New Communication Technologies and the Internet. He received a PhD in Computer Science from University College London and also holds a BSc in Computer Engineering from the University of Manchester. His past teaching experience includes visiting lectureships at UK universities and the University of Cyprus. He has participated in several large-scale research projects funded by the European Commission in the area of real-time multimedia communication over the Internet and served on scientific conference committees. Research work generally falls in the area of computer networks. Dr. Lambrinos is the Principal Investigator of the research program “e-park” (www.e-park.eu). For more detailed information on current research activities please visit the Ubiquitous Computing and Smart Living lab web page.
Keywords: computer